2011
DOI: 10.1002/stem.633
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Potential of Human Postnatal Mesenchymal Stem Cells, Mesoangioblasts, and Multipotent Adult Progenitor Cells Reflected in Their Transcriptome and Partially Influenced by the Culture Conditions

Abstract: Several adherent postnatal stem cells have been described with different phenotypic and functional properties. As many of these cells are being considered for clinical therapies, it is of great importance that the identity and potency of these products is validated. We compared the phenotype and functional characteristics of human mesenchymal stem cells (hMSCs), human mesoangioblasts (hMab), and human multipotent adult progenitor cells (hMAPCs) using uniform standardized methods. Human MAPCs could be expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 50 publications
6
141
0
1
Order By: Relevance
“…We also demonstrated that MAPC cells can provide stromal support for MDSderived hematopoietic cells. We know from previous microarray data that human MAPCs express hematopoiesis-supporting cytokines SCF, CXCL5, IL-8, IL-11, TGF-1β, VEGF, ANGPT1 and SPARC [11], but future studies will need to investigate the secretome of MAPC cells when co-cultured with MDS BM cells to determine the responsible factor(s) for hematopoietic improvement seen in MDS. A general secretome analysis of human MAPC cells revealed the presence of molecules that are involved in extracellular matrix regulation and angiogenesis as well as secretion of cytokines that influence cells from the innate and adaptive immune system in their recruitment and effector function [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that MAPC cells can provide stromal support for MDSderived hematopoietic cells. We know from previous microarray data that human MAPCs express hematopoiesis-supporting cytokines SCF, CXCL5, IL-8, IL-11, TGF-1β, VEGF, ANGPT1 and SPARC [11], but future studies will need to investigate the secretome of MAPC cells when co-cultured with MDS BM cells to determine the responsible factor(s) for hematopoietic improvement seen in MDS. A general secretome analysis of human MAPC cells revealed the presence of molecules that are involved in extracellular matrix regulation and angiogenesis as well as secretion of cytokines that influence cells from the innate and adaptive immune system in their recruitment and effector function [21].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with MSCs, they have significantly greater proliferation potential and differentiation potential (e.g., functional endothelium in vitro as well as in vivo) [11]. Like MSCs, MAPC cells have potent immunomodulatory effects in T cells [12][13][14], are nonimmunogenic for T-cell proliferation and cytokine production and even suppress T-cell activation and proliferation induced by alloantigens and mitogens in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a hypoxic environment during culture, supplementing with growth factors including basic fibroblast growth factor, epidermal growth factor, and platelet-derived growth factor, and maintaining cells at subconfluent levels are important parameters that are associated with these improvements [11,12]. These conditions are known to influence retention of telomerase activity and maintenance of signaling pathways that are associated with pluripotency in other environments [13].…”
Section: Cell Populations Serving As Potential Reference Cell Bank(s)mentioning
confidence: 99%
“…16,17 MAPCs are also capable of forming the three germ lineages, including the mesoderm that gives rise to bone tissue when dexamethasone is supplemented. 18,19 Recent studies demonstrate that clinical grade human MAPCs (Multistem Ò ) offer clinical relevance for the treatment of autoimmune disorders and cardiac infarction (ClinicalTrials.gov NCT00677859, NCT00677222); however, no in vivo applicability studies for bone regeneration have been reported.…”
Section: Introductionmentioning
confidence: 99%